1997
DOI: 10.1111/j.1600-0765.1997.tb00540.x
|View full text |Cite
|
Sign up to set email alerts
|

Effective group behavioral intervention for older periodontal patients

Abstract: A randomized clinical trial assessed the effect of a group-based behavior modification intervention on oral hygiene skills, adherence and clinical outcomes for older periodontal patients. Subjects (n = 107) were aged 50-70 yr with moderate periodontal disease. They were randomly assigned to usual care or intervention. Intervention consisted of 5 weekly, 90-min sessions that included skill training, self-monitoring, weekly feedback about bleeding points and group support focused on long-term habit change. Four-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
58
0
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(62 citation statements)
references
References 38 publications
3
58
0
1
Order By: Relevance
“…Active psychological intervention versus no intervention [6][7][8][9] Active psychological intervention versus educational intervention 7,8 Active psychological intervention versus attention control 7,9 Four studies (Little 1997;Stewart 1991;Stewart 1996;Weinstein 1996) provided some evidence that psychological interventions can lead to improvement in plaque scores and possibly decreased gingival bleeding compared with no interventions. Similarly, 2 studies 6,7 provided evidence that psychological interventions led to improved brushing behaviors over attention and educational controls.…”
Section: Resultsmentioning
confidence: 97%
“…Active psychological intervention versus no intervention [6][7][8][9] Active psychological intervention versus educational intervention 7,8 Active psychological intervention versus attention control 7,9 Four studies (Little 1997;Stewart 1991;Stewart 1996;Weinstein 1996) provided some evidence that psychological interventions can lead to improvement in plaque scores and possibly decreased gingival bleeding compared with no interventions. Similarly, 2 studies 6,7 provided evidence that psychological interventions led to improved brushing behaviors over attention and educational controls.…”
Section: Resultsmentioning
confidence: 97%
“…Four studies (Frenkel et al, 2002;Gammack and Pulisetty, 2009;Khanagar et al, 2014;Reed et al, 2006) did not evaluate the oral health of the elderly. Two articles described the effects of an educational program on oral health provided to the elderly, not to the caregivers (Little et al, 1997;Persson et al, 1998) and two articles were review articles (Watt and Marinho 2005;Stein and Henry, 2009). The five included studies reported the effect of the caregivers' oral health education on the oral health status of 602 combined elderly residents (Boczko et al, 2009;Frenkel et al, 2001;Isaksson et al, 2000;Nicol et al, 2005;Portella et al, 2013).…”
Section: Literature Searchmentioning
confidence: 97%
“…Also excluded were patients who had undergone extensive nonsurgical periodontal treatment within the previous 6 months, periodontal surgery within the previous 2 years or any active or planned periodontal treatment other than routine dental prophylaxis [23]. All patients in this study gave consent for participation in the study.…”
Section: Subjectsmentioning
confidence: 99%